Quebec-Ontario Relations : A Shared Destiny? - Côte, Louis, 1949-; Savard, Jean-François, 1973-; Brassard, Alexandre, 1972- (Book collections on Project MUSE., 2013)
Our methodology combined historical and comparative approaches. The first part focuses specifically on the origin and current state of relationships betweens the two provinces. It offers a "big picture" view of inter-relationships from a number of perspectives (political, economic, social, and public policy). The second part compares key public policy issues in the provinces in a wide range of key fields. The analyzes provided Illustrate the similarities and differences betweens Ontario and Quebec, and provide a better understanding of the issues and policies that affect Ontario-Quebec relations."--Pub. desc.